The simplicity of dementia : a guide for family and carers - Buijssen, H. P. J. (Jessica Kingsley Publishers, 2005)
This book offers an accessible and sympathetic introduction for relatives, carers and professionals looking after or training to work with people with dementia. Drawing on the two 'laws of dementia', the author explains the causes of communication problems, mood disturbances and 'deviant' behaviours, with particular emphasis on how these are experienced by dementia sufferers themselves. Case examples demonstrate the typical symptoms and progression of dementia, and clear guidance is provided on how to support dementia sufferers at every stage and help them deal with the challenges posed by the.